2016
DOI: 10.1111/imm.12569
|View full text |Cite
|
Sign up to set email alerts
|

A peptide tetramer Tk‐tPN induces tolerance of cardiac allografting by conversion of type 1 to type 2 immune responses via the Toll‐like receptor 2 signal‐promoted activation of the MCP1 gene

Abstract: SummaryThe plant protein trichosanthin (Tk) and its derived peptide tetramer TktPN have been shown to stimulate the type 2 immune responses for treating autoimmune disease. This work explores the possibility of using Tk-tPN as a non-toxic immunosuppressant to induce transplantation tolerance using the mechanisms by which T-cell-mediated immune responses are transferred from type 1 to type 2 through innate immunity-related pathways. Immunocytes and cytokine secretions involved in the mouse cardiac allografting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although suppressive characteristic of CD8 + CD28 − Ts cells have been reported ( 19 , 20 , 24 ), there are other studies, which implies their cytotoxicity ( 31 ). In this study, we set up a CFSE-based assay as our previous report ( 24 ) and ruled out the cytotoxicity of CD8 + CD28 − Ts cells toward the priming APCs, which might contribute to the donor-specific suppression of proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although suppressive characteristic of CD8 + CD28 − Ts cells have been reported ( 19 , 20 , 24 ), there are other studies, which implies their cytotoxicity ( 31 ). In this study, we set up a CFSE-based assay as our previous report ( 24 ) and ruled out the cytotoxicity of CD8 + CD28 − Ts cells toward the priming APCs, which might contribute to the donor-specific suppression of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best characterized CD8 + Tregs populations is the CD8 + CD28 − T suppressor cells, which play a significant role in various diseases ( 16 18 ) including allogeneic transplantation ( 19 ). Human allospecific CD8 + CD28 − T cells have been generated in vitro when repeatedly stimulated with allogeneic antigen-presenting cells (APCs) for several rounds and has supplemental recombinant human IL-2 ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies demonstrated that DQ alleles play a critical role in TCS-induced immunosuppression by down-regulating function of CD8 cells [12] , and depletion of CD8 cells from total T cells or blocking expression of HLA-DQ molecules could effectively diminish TK's inhibitory activity against immune response [13] . Recently, Yang N et al reported that a TCS-derived peptide can suppress type 1 immune response by TLR2-dependent activation of CD8(+)CD28(-) tregs [14] , and suggest new eras in using TCS-tPN, a homo-tetramer, as a therapeutic reagent for Th1-dominant immunological diseases [14] and inducing tolerance of cardiac allografting [15] . And studies in major histocompatibility complex-mismatched mouse skin allograft also revealed the inspiring results of TCS effectively preventing allograft rejection, perhaps by reducing IL-2 and IFN-γ expression and inducing IL-4 and IL-10 expression [16] .…”
Section: Research Highlightmentioning
confidence: 99%